O DIREITO E A SIMBOLOGIA MITOLÓGICA DA ALMA FEMININA - Konzen, Marita Beatriz (Revista Liberato, 2013)
This text examines the course of woman in the history of humanity. Taken from the main feminine divinities that are found in Greek mythology it is presented that current Law is inherited from Greco-Roman Law; however, the search for the “feminine soul” in mythological goddesses required considerable assistance from the psychological hermeneutics. The equality of the sexes, constitutionally specified, does not reach the dreamed of praxis, as we have not managed to understand that, above all else, Law needs to allow the introduction of a feminist juridical hermeneutics, along with men, from degree courses in Law through to the collective decisions of the supreme courts, “embracing” the hermeneutics of psychology, psychiatry, anthropology, history, philosophy and sociology. Consequently, changing the social indifference over the differences between men and women is one of the presuppositions for the realization of the much dreamed respect to human rights and, as a consequence, “experiment” with a democratic society.